Jovens estudantes pobres: significados atribuídos às práticas pedagógicas denominadas inovadoras por seus professores - Analise de Jesus da Silva (2007)
This research investigates the meaning attributed by young students, with age between 14 and 24 years old, poor, to the activities proposed by their teachers on everyday school life, which take place on the classroom, and are denominated by the teachers as innovative pedagogical practices, in schools with the night-time classes, in Belo Horizonte, and the educational theory applied in called Escola Plural. This central question emerges from the statement, by the teachers, that the young student does not take part in those innovative classes. With a qualitative perspective of research, there were interviewed 44 poor young students and four of their high-school teachers. Individual and collective interviews were carried out. The 44 young students and the four teachers are of four different schools from the Belo Horizontes Educational System. Classes of the four teachers were observed and analyzed. Were also analyzed documents provided by the Citys Education Secretariat, by the schools and by research groups, their results were incorporated in this research. Among the findings of this investigation, two are to be highlighted. The first is that an approach related to the life experiences of the poor young students is almost inexistent in the general context of the schools where this research took place. A second finding is the high number of young students that do not take part in any collectivity, neither cultural, nor sportive, nor religious. The majority of the young people interviewed do not belong to any kind of collective movement. Pointing in response to central question we highlight two possible considerations. The first consideration is that the great majority of the young people interviewed do adhere to the different classes. The second consideration is the existence of, not one, but various meanings attributed by the young students. These meanings are what move them in relation to the experience of the innovative pedagogical practices proposed by their teachers. During the accomplishment of this research we notice the shortage of bibliography concerning young students without insertion in collective movements.